2012
DOI: 10.1016/j.molcel.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression Noise and Acetylation Profiles Distinguish HDAC Functions

Abstract: Gene expression shows a significant variation (noise) between genetically identical cells. Noise depends on the gene expression process regulated by the chromatin environment. We screened for chromatin factors that modulate noise in S. cerevisiae and analyzed the results using a theoretical model that infers regulatory mechanisms from the noise vs. mean relationship. Distinct activities of the Rpd3(L) and Set3 histone deacetylase complexes were predicted. Both HDACs repressed expression. Yet, Rpd3(L)C decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
121
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 56 publications
10
121
0
Order By: Relevance
“…Consistent with SETD5 being recruited with PAF1C and NCoR to actively transcribed genes, Setd5 null mESCs have slightly increased H3K36 methylation, a cotranscriptional histone modification that is enriched over the coding region of genes. Moreover, we did not observe any global changes in H3K4 methylation, which is typically associated with active promoter regions, suggesting that SETD5/HDAC3 repression might mostly target transcriptional elongation, as does the yeast SET3C complex (Weinberger et al, 2012). In mammals, several HATs and HDACs have been shown to be targeted to the transcribed regions of active genes by phosphorylated RNAP II (Wang et al, 2009).…”
Section: Lhx1mentioning
confidence: 69%
“…Consistent with SETD5 being recruited with PAF1C and NCoR to actively transcribed genes, Setd5 null mESCs have slightly increased H3K36 methylation, a cotranscriptional histone modification that is enriched over the coding region of genes. Moreover, we did not observe any global changes in H3K4 methylation, which is typically associated with active promoter regions, suggesting that SETD5/HDAC3 repression might mostly target transcriptional elongation, as does the yeast SET3C complex (Weinberger et al, 2012). In mammals, several HATs and HDACs have been shown to be targeted to the transcribed regions of active genes by phosphorylated RNAP II (Wang et al, 2009).…”
Section: Lhx1mentioning
confidence: 69%
“…Eviction of acetylated nucleosomes ahead of Pol II permits efficient elongation, whereas reassembly of deacetylated nucleosomes behind the elongating polymerase prevents initiation at spurious sites. Consistent with this scenario, mutations in histone chaperones that promote nucleosome assembly/disassembly, or in enzyme complexes that catalyze or erase histone modifications associated with gene bodies (e.g., H3K9/14 and H4 acetylation, H2B ubiquitylation, and H3K36 di-and trimethylation), affect transcriptional consistency in yeast (49,(53)(54)(55).…”
Section: Discussionmentioning
confidence: 88%
“…Variations in gene expression patterns within a single cell can be assessed by comparing the levels of two different reporter genes driven off the same promoter (intrinsic noise), whereas those that occur between cells (extrinsic noise) can be examined in many ways, including single-cell RNA sequencing, the technique we have used here (44)(45)(46). Cell-to-cell variability in gene expression reflects stochastic variation, differences in cell state or environmental input, and gene regulatory processes including the frequency and robustness of transcriptional initiation (46), the relative abundance of transcriptional regulators (47,48), the size and frequency of transcriptional bursts (49), the spatial organization of the genome (50), and the relative efficiency of transcription vs. translation (51) (reviewed in refs. 45,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might occur by influencing the frequency of transcription initiation (defined as loading of the RNA polymerase), by transition to the elongating form or by impeding the rate of the transcribing RNA polymerase. Evidence for co-repressor proteins exerting exactly this kind of fine transcriptional control came initially from yeast, in which chromatin-modifying proteins were shown to influence transcriptional 'noise' (Huang, 2009) and absolute levels of transcription (Raser and O'Shea, 2004;Weinberger et al, 2012). More recently, it was shown that the lysine deacetylase-containing NuRD complex can influence both of these distinct aspects of transcriptional output in mammalian cells, and that this level of transcriptional control is essential to maintain the developmental responsiveness of pluripotent cells (Reynolds et al, 2012a).…”
Section: Repressors As Fine-tuners Of Gene Expression and Cell Fatementioning
confidence: 99%